The Importance of Mechanical Forces for in vitro Endothelial Cell Biology - Gordon, Emma; Schimmel, Lilian; Frye, Maike (Frontiers in Physiology, 2020)
Blood and lymphatic vessels are lined by endothelial cells which constantly interact with their luminal and abluminal extracellular environments. These interactions confer physical forces on the endothelium, such as shear stress, stretch and stiffness, to mediate biological responses. These physical forces are often altered during disease, driving abnormal endothelial cell behaviour and pathology. Therefore, it is critical that we understand the mechanisms by which endothelial cells respond to physical forces. Traditionally, endothelial cells in culture are grown in the absence of flow on stiff substrates such as plastic or glass. These cells are not subjected to the physical forces that endothelial cells endure in vivo, thus the results of these experiments often do not mimic those observed in the body. The field of vascular biology now realise that an intricate analysis of endothelial signalling mechanisms requires complex in vitro systems to mimic in vivo conditions. Here, we will review what is known about the mechanical forces that guide endothelial cell behaviour and then discuss the advancements in endothelial cell culture models designed to better mimic the in vivo vascular microenvironment. A wider application of these technologies will provide more biologically relevant information from cultured cells which will be reproducible to conditions found in the body.